ANALISIS PENGENDALIAN PERSEDIAAN OBAT ANTIBIOTIK DI RS MEILIA PADA TAHUN 2014 DENGAN MENGGUNAKAN METODE ANALISIS ABC INDEKS KRITIS - Octaviany, Myrna (UI Scholars Hub, 2018)
The purpose of this research is to analyze antibiotics inventory control using ABC critical index method at Meilia Hospital in 2014. The design of this research is a descriptive quantitative research. In this research the data is based on the consumed antibiotics in January to December 2014 and the critical index value of antibiotics. The result showed that the group A consisted of 10 items with a value of Rp 2.114.748.870,- (39.91%). The group B consisted of 45 items with a value of Rp 2.380.506.460,- (44.92%). The group C consisted of 110 items with a value of Rp 803.183.274,- (15.17%). An inventory control analysis was done by calculating EOQ and ROP of the group A. The three methods of forecasting were used in this research, i.e Single Smoothing Exponential, 3 period Moving Average, and 3 period Weighted Moving Average. Forecasting method that will be used is determined by the level of accuracy and the influence of forecast result on hospital cost